An investigation of teacher-provided versus student-made vocabulary notebooks - Elahe Moladoust,; Sasan Baleghizadeh, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
Vocabulary notebooks are viewed as a self-study strategy, and they have been widely used in many EFL contexts (Nation, 2011). Given this, the challenge is that EFL learners may not be able to decide what sort of knowledge to acquire about a certain word. Anchored in this challenge, the present study compares teacher-provided vocabulary notebooks (TPVNs) with student-made vocabulary notebooks (SMVNs). The participants were 28 elementary teenage EFL learners divided into two experimental groups: TPVN and SMVN. The results indicated that the TPVN group outperformed the SMVN group, especially in their productive knowledge of orthography and productive knowledge of meaning and form. Three days after the post-test, a number of participants from both groups were interviewed randomly to explore their viewpoints about each kind of notebook. It was found out that the SMVN group did not look some of the words up for three reasons: (a) they thought they could guess the correct meaning from the context, (b) they were at times lazy, and (c) they did not have enough time. The results of this study have implications for EFL teachers and materials writers.